Zr-based metal–organic frameworks: design, synthesis, structure, and applications - Bai, Yan; Dou, Yibo; Xie, Lin-Hua; Rutledge, William; Li, Jian-Rong; Zhou, Hong-Cai (Chemical Society reviews, 2016)
Among the large family of metal–organic frameworks (MOFs), Zr-based MOFs, which exhibit rich structure types, outstanding stability, intriguing properties and functions, are foreseen as one of the most promising MOF materials for practical applications. Although this specific type of MOF is still in its early stage of development, significant progress has been made in recent years. Herein, advances in Zr-MOFs since 2008 are summarized and reviewed from three aspects: design and synthesis, structure, and applications. Four synthesis strategies implemented in building and/or modifying Zr-MOFs as well as their scale-up preparation under green and industrially feasible conditions are illustrated first. Zr-MOFs with various structural types are then classified and discussed in terms of different Zr-based secondary building units and organic ligands. Finally, applications of Zr-MOFs in catalysis, molecule adsorption and separation, drug delivery, and fluorescence sensing, and as porous carriers are highlighted. Such a review based on a specific type of MOF is expected to provide guidance for the in-depth investigation of MOFs towards practical applications.